2019
DOI: 10.1016/j.immuni.2019.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Interleukin-6 Signaling in Clinic

Abstract: Interleukin-6 (IL-6) is a pleiotropic cytokine with roles in immunity, tissue regeneration, and metabolism. Rapid production of IL-6 contributes to host defense during infection and tissue injury, but excessive synthesis of IL-6 and dysregulation of IL-6 receptor signaling is involved in disease pathology. Therapeutic agents targeting the IL-6 axis are effective in rheumatoid arthritis, and applications are being extended to other settings of acute and chronic inflammation. Recent studies reveal that selective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
586
1
14

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 667 publications
(604 citation statements)
references
References 150 publications
(139 reference statements)
3
586
1
14
Order By: Relevance
“…IL-6 has prominent proinflammatory properties (see the figure). IL-6 can signal through two main pathways referred to as classic cis signaling or trans signaling (10). In cis signaling, IL-6 binds to membrane-bound IL-6 receptor (mIL-6R) in a complex with gp130; downstream signal transduction is mediated by JAKs (Janus kinases) and STAT3 (signal transducer and activator of transcription 3).…”
mentioning
confidence: 99%
“…IL-6 has prominent proinflammatory properties (see the figure). IL-6 can signal through two main pathways referred to as classic cis signaling or trans signaling (10). In cis signaling, IL-6 binds to membrane-bound IL-6 receptor (mIL-6R) in a complex with gp130; downstream signal transduction is mediated by JAKs (Janus kinases) and STAT3 (signal transducer and activator of transcription 3).…”
mentioning
confidence: 99%
“…We hypothesize that JAK inhibitors could be superior agents in terms of attenuating the cytokine storm caused by COVID-19 relative to existing anti-IL6 agents, which consist of injectable monoclonal antibodies that inhibit the interaction between IL-6 and its receptor IL-6R (26). In contrast, JAK inhibitors are available as drugs administered orally, with very well characterized pharmacodynamics and pharmacokinetics, and may provide a more appropriate strategy to transiently tone down the cytokine storm to prevent ARDS and fulminant myocarditis.…”
Section: Incb54707mentioning
confidence: 99%
“…Next, we quantified mRNA expression by RNA sequencing and compared transcriptome signatures of SFs between the 10 conditions (i.e., non-stimulated, IFN-α, IFN-γ, TNF-α, IL-1β, IL-6/sIL-6R, 7 IL-17, TGF-β1, IL-18 or 8-mix) and the diseases (i.e., RA, OA). Principal component analysis (PCA) of gene expression levels showed that the 8-mix condition induced a distinct transcriptome signature compared with the other stimulatory conditions, corresponding to the first component (PC1 in Fig.…”
Section: Cytokine Mixture Induced a Distinctive Transcriptome Signatumentioning
confidence: 99%
“…2B). For instance, the markedly high expression of IL6, which codes a pivotal cytokine in RA pathogenesis with a diverse repertoire of functions (e.g., osteoclast differentiation) (7), was achieved by the 8-mix stimulation (Primary component loading on PC1 = -0.76, PC2 = 0.26.…”
Section: Cytokine Mixture Induced a Distinctive Transcriptome Signatumentioning
confidence: 99%
See 1 more Smart Citation